The state of budget financing of local economic development in Ukraine: regional dimension. - Bak, N. (Східна Європа: економіка, бізнес та управління., 2022)
The article emphasizes that the current state of local economic development (further – “LED”) supply in Ukraine is characterized by the dominance of the budget method of formation and use of financial resources. It is proved that two types of factors influence the effectiveness of this method: national characteristics of the mechanism of budget financing of LED and due to the specifics of territorial needs and their resourcefulness. It was found that the combined impact of these factors has led to low effectiveness of budget funding for LED in the Chernivtsi region. The main source of this funding is the State Budget of Ukraine, including the State Fund for Regional Development. At the same time, the transfer mechanism is activated as much as possible. Its disadvantage is the subjectivity of budget resource allocation. Under quarantine restrictions, the state of LED's funding has deteriorated. The article proposes several measures aimed at reducing the negative impact of macroeconomic factors and improving the mechanism of budget financing of LED.
Keywords: local economic development (LED), budget financing, local budgets, investment program, transfer